Proliferation of Highly Cytotoxic Human Natural Killer Cells by OX40L Armed NK-92 With Secretory Neoleukin-2/15 for Cancer Immunotherapy - Guo, Meng; Sun, Chen; Qian, Yuping; Zhu, Liye; Ta, Na; Wang, Guangjian; Zheng, Jianming; Guo, Fengfu; Liu, Yanfang (Frontiers in Oncology, 2021)
Adoptive natural killer (NK) cell transfer has been a promising immunotherapy for malignancies, requiring administration sufficient activated cells to ensure treatment effectiveness. However, paucity of clinical grade and low-cost method for large-scale cell expansion limits the feasibility. Here we developed a feeder-based NK cell expansion approach that uses OX40L armed NK-92 cell with secreting neoleukin-2/15 (Neo-2/15), a hyper-stable mimetic with high affinity to IL-2Rβγ. The novel feeder cells (NK92-Neo2/15-OX40L) induce expansion of NK cells with increasing 2180-fold (median; 5 donors; range, 1767 to 2276) after 21 days of co-culture without adding cytokines. These cells were highly cytotoxic against Raji cells and also against several solid tumors in vivo. Mechanistically, NK92-Neo2/15-OX40L induced OX40 and OX40L expression on expanded NK cells and fatherly promoted OX40-OX40L positive feedback loop, which promoting NK cell function. Our data provided a novel NK cell expansion methodology and mechanistic insights into OX40-OX40L axis regulating NK cell expansion.